Nut Crops (IntechOpen, 2023)
Nut Crops - New Insights provides a comprehensive overview of recent developments in nut crop cultivation and dietotherapy with nuts. It also examines the nutritional composition and health-promoting effects of nuts. Written and reviewed by experts in horticulture, agriculture, and food and medical sciences, this book opens new possible research paths for further novel developments in nut crops.